2010
DOI: 10.1515/znc-2010-7-804
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholinesterase Inhibitory Activity of Uleine from Himatanthus lancifolius

Abstract: Application of acetylcholinesterase (AChE) inhibitors is the primary treatment for Alzheimer’s disease. Alkaloids, such as physostigmine, galanthamine, and huperzine A, play an important role as AChE inhibitors. The aim of this work was to evaluate Himatanthus lancifolius (Muell. Arg.) Woodson, a Brazilian species of Apocynaceae, and its main indole alkaloid uleine, in order to identify new AChE inhibitors. The plant fluid extract, fractions, and uleine were tested for AChE inhibitory activity using Ellman’s c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 24 publications
3
22
0
1
Order By: Relevance
“…Seidl et al [20] conducted a study to determine if there were any AChE inhibiting properties from the Himatanthus lancifolius extract and uliene in vitro . The dichloromethane (DCM), and ethyl acetate (EtOAc), fractions showed significant AChE inhibitory effects.…”
Section: Naturally Derivedmentioning
confidence: 99%
“…Seidl et al [20] conducted a study to determine if there were any AChE inhibiting properties from the Himatanthus lancifolius extract and uliene in vitro . The dichloromethane (DCM), and ethyl acetate (EtOAc), fractions showed significant AChE inhibitory effects.…”
Section: Naturally Derivedmentioning
confidence: 99%
“…Rich fractions of lipophilic alkaloids were able to act as AChE-I and uleine ( Figure 1) was isolated from them. 22,26 This alkaloid was firstly isolated from the root bark of Aspidosperma ulei Mgf and was studied from a chemical and synthetic point of view. [27][28][29][30] Furthermore, this alkaloid and its related derivatives were also studied for their anticancer properties, 30 and, more recently, alkaloids-enriched fractions were also studied for their in vitro anti-inflammatory properties.…”
Section: Indole Alkaloids and Related Compoundsmentioning
confidence: 99%
“…26 For this reason, uleine is considered as a new possible candidate for the future development of new anti-AD drugs, but no reports about safety, efficacy, and human studies specific to cognition have been reported to date. 22,26 …”
Section: Indole Alkaloids and Related Compoundsmentioning
confidence: 99%
“…Uleine stimulated a maximum nitric oxide production in the concentrations of 0.1 µg/mL (20.9 ± 1.4 µM) and 1 µg/mL (41.1 ± 0.2 µM) [16] and exhibited high level of acetylcholinesterase inhibition [17]. Uleine was evaluated for cytotoxicity against 65 cancer cell lines panel and it was inactive in all of them [18].…”
Section: Introductionmentioning
confidence: 99%